The Effect of Pedagogic and Professional Competency on the Performance of Primary School Teachers in Kisam Tinggi District - Putra, Ipansa; Fitria, Happy; Puspita, Yenny (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine and analyze the effect of pedagogic competence and professional competence on the performance of elementary school teachers in Kisam Tinggi District. This research is a type of quantitative. The instrument used is a questionnaire. The prerequisite tests to be carried out are normality test, linearity test, and data analysis using simple regression. The results of data analysis can be explained that overall the pedagogical competence of elementary school teachers in Kisam Tinggi District is in the good category seen from the distribution of the highest data in the good category. From this explanation it can be concluded that there is a positive and significant influence between pedagogical competence on the performance of elementary school teachers in Kisam Tinggi District. In addition, it is also seen from the results of the calculation of the product moment correlation that there is a positive influence between professional competence on the performance of elementary school teachers in Kisam Tinggi District